Esterification of Benzyl Alcohol with Acetic Acid over Mesoporous H-ZSM-5 - Desy Tri Kusumaningtyas; Didik Prasetyoko; Suprapto Suprapto; Sugeng Triwahyono; Aishah Abdul Jalil; Afifah Rosidah (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
In this study, the performance of mesoporous ZSM-5 has been studied on the esterification of acetic acid (AA) with benzyl alcohol (BA). The mesoporous ZSM-5 catalyst has been synthesized with the variation of aging time i.e. 6, 12, and 24 hours at the same temperature, 70 °C. The cation exchange of Na-ZSM-5 to H-ZSM-5 was performed before the catalytic activity test. The acidity type and amount of solids were determined by FT-IR spectroscopy using pyridine as a probe molecule. The characterization by pyridine adsorption showed that at a higher mesoporous surface area, the number of Lewis acid was increased. The highest mesoporous surface area, Lewis, and Brönsted acid sites were obtained by sample which has the lowest crystallinity, i.e. 255.78 m2/g, 0.2732 mmol/g, and 0.20612 mmol/g, respectively. Influence of mesoporous volume was studied on the catalytic activity of the mesoporous ZSM-5 in the esterification reaction. Conversion of acetic acid in the esterification reaction for samples of    HZ-6, HZ-12, and HZ-24 were obtained by titration methods, i.e. 39.59, 36.39, and 32.90 %, respectively. Hence, the reaction temperature of 393 K, molar ratio 1:4 (AA:BA) and catalyst loading 5 % were selected as an optimum reaction parameters.